Pengaruh Kompensasi, Promosi Jabatan dan Beban Kerja Terhadap Kinerja Karyawan Field Force PT Anugrah Argon Medica Cabang Bandung - Miftah, Adis Abdul; Jaya, Rama Chandra (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
Employee performance is essential to an organization's ability to achieve its goals. A particular organization or institution's success dramatically affects its employees' working conditions. To improve employee performance, companies do various things, such as providing adequate compensation and implementing job promotions that can be implemented fairly by considering aspects of meeting requirements. Through this process, employees are expected to maximize their responsibilities for their work, as well as the workload given. This study aims to determine the effect of compensation, job promotions, and workload on employee performance at PT. Anugrah Argon Medica, Bandung branch. The research method used in this study uses a quantitative approach with a descriptive verification method. The data type used is primary data with a questionnaire data collection technique. The population in this study were employees of PT. Anugrah Argon Medica, Bandung branch, totaling 45 employees. The sampling technique used was a nonprobability sampling technique with total sampling. Data analysis in this study used multiple linear regression analysis. The study showed that the distribution of compensation showed somewhat appropriate results, job promotions in the high or very appropriate category, a reasonably high workload, and employee performance assessments classified as moderate or relatively high. The results of the hypothesis testing show that partially (1) Compensation has a significant positive effect on employee performance, (2) Job promotion has a significant positive effect on employee performance, (3) workload has a significant negative effect on employee performance, and (4) simultaneously compensation, job promotion and workload simultaneously have a significant positive effect on employee performance